1982
DOI: 10.1071/wr9820409
|View full text |Cite
|
Sign up to set email alerts
|

Ecology of the Feral Cat, Felis catus (L.), in Souht-Eastern Australia III.* HOme Ranges and Population Ecology in Semiarid North-West Victoria

Abstract: This paper reports home range sizes and population ecology of feral cats in a 19000-ha study area situated in the Victorian Mallee. Movements of six cats were monitored by radio-tracking for 8-21 months. Adults maintained discrete home ranges; areas varied from 3 . 3 to 9 . 9 (mean 6.2) km2 for males and from 0 . 7 to 2 . 7 (mean 1 ,7) km2 for females. Rabbit warrens, hollow logs and dense thickets were favoured daytime refuges. Mean daily straight-line distances moved bet-veen daytime refuges varied from 0.06… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
78
1

Year Published

1992
1992
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(89 citation statements)
references
References 14 publications
10
78
1
Order By: Relevance
“…Female cats reach sexual maturity between 6 and 8 months and males between 8 and 10 months and can breed 2-3 times a year. However, reproduction can be delayed (Jones and Coman 1982;Say et al 1999) as shown by Bester et al (2002), who reported that a drastic decrease of feral cats following eradication efforts on subantarctic Marion Island caused a decline in pregnancy rates and fecundity, possibly owing to a lower encounter rate between the sexes. Control efforts need to minimise gene flow to no more than one migrant per generation in order to decrease genetic diversity (Wright 1969) and thus create small or fragmented populations in which inbreeding is more likely to occur.…”
Section: Discussionmentioning
confidence: 99%
“…Female cats reach sexual maturity between 6 and 8 months and males between 8 and 10 months and can breed 2-3 times a year. However, reproduction can be delayed (Jones and Coman 1982;Say et al 1999) as shown by Bester et al (2002), who reported that a drastic decrease of feral cats following eradication efforts on subantarctic Marion Island caused a decline in pregnancy rates and fecundity, possibly owing to a lower encounter rate between the sexes. Control efforts need to minimise gene flow to no more than one migrant per generation in order to decrease genetic diversity (Wright 1969) and thus create small or fragmented populations in which inbreeding is more likely to occur.…”
Section: Discussionmentioning
confidence: 99%
“…Cats were classified according to sex, age, month and season of capture (see Daniels 1997), with age classed on the basis of body weight (Jones and Coman 1982) as: females: < 1.6 kg = 'juvenile', 1.6-2.5 kg = 'subadult', > 2.5 kg = 'adult', males: < 2.2 kg = 'juvenile', 2.2-3.5 kg = 'subadult', > 3.5 kg = 'adult'.…”
Section: Methodsmentioning
confidence: 99%
“…Other feral populations appear to have no seasonal variation in testes mass, but do show differences in other reproductive parameters (Jones and Coman 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Density estimates in New Zealand range from 1 to 7/km 2 in farms and rural areas (Fitzgerald & Karl, 1986;Jones, 1977, Jones & Coman, 1982Langham, 1992;Langham & Porter, 1991). The significant variance in reported density means that estimates from other countries or cities are not reliable measures for local decision-making.…”
Section: Introductionmentioning
confidence: 99%